Suluk Wujil: Model of Normatif-Spiritual Management in Islamic Education - Hafidl, Noor; Purwanto, Purwanto; Suharto, Toto (Pascasarjana IAIN Kudus, 2024)
The present study offers an analytical review of the content of Suluk Wujil, entitled